2021
DOI: 10.3390/cancers13225593
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Osteoclasts into Bone-Protective, Tumor-Suppressing Cells

Abstract: Osteoclasts are a driver of a vicious bone-destructive cycle with breast cancer cells. Here, we examined whether this vicious cycle can be altered into a beneficial one by activating Wnt signaling with its activating agent, BML284. The conditioned medium, derived from Wnt-activated RAW264.7 pre-osteoclast cells (BM CM), reduced the proliferation, migration, and invasion of EO771 mammary tumor cells. The same inhibitory effect was obtained with BML284-treated primary human macrophages. In a mouse model, BM CM r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 42 publications
(62 reference statements)
0
24
0
Order By: Relevance
“…We have previously shown that overexpressing Lrp5, β-catenin, Snail, or Akt converted many types of bone cells such as mesenchymal stem cells (MSCs), osteoblasts, osteocytes, and osteoclasts into induced tumor-suppressing (iTS) cells 3 - 7 . iTS cells secrete well-known tumor-suppressing proteins such as p53 and Trail, as well as a group of uncommon tumor suppressors 3 , including Hsp90ab1, calreticulin, and peptidylprolyl isomerase B.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that overexpressing Lrp5, β-catenin, Snail, or Akt converted many types of bone cells such as mesenchymal stem cells (MSCs), osteoblasts, osteocytes, and osteoclasts into induced tumor-suppressing (iTS) cells 3 - 7 . iTS cells secrete well-known tumor-suppressing proteins such as p53 and Trail, as well as a group of uncommon tumor suppressors 3 , including Hsp90ab1, calreticulin, and peptidylprolyl isomerase B.…”
Section: Introductionmentioning
confidence: 99%
“…The anti-tumor action of CM was resistant to nuclease treatment and filtering with a 3-kD cutoff, and we thus focused on the proteomes as anti-tumor agents. 18 Since the previous work was mainly conducted using mouse cells, the question herein was whether human-derived MSCs, which have been used in regenerative medicine and can be harvested from bone marrow, 19 would be used to generate iTSCs and tumor-suppressive proteomes. We examined commercially available human MSCs, as well as adherent cells isolated from a human bone marrow aspirate-derived MSC (BMSCs).…”
Section: Introductionmentioning
confidence: 99%
“…Similar antitumor capability was observed in MSCs generated by overexpressing LRP5, β-catenin, Snail, or Akt [203]. Activation of WNT signaling in osteoclasts, osteoblasts, and cancer cells resulted in their conversion to tumor-suppressive cells with secretomes enriched with Hsp90ab1, enolase 1 (Eno1), moesin (MSN), and ubiquitin C (Ubc), which acted as atypical tumorsuppressors [204][205][206]. Osteoclast secretome-derived Hsp90ab1 and Eno1 inhibited tumor progression by suppressing TGF-ß signaling and interacting with CD44, facilitating tumor cell killing by natural killer (NK) cells [204,207].…”
Section: Novel Approaches To Treat Bone Metastasesmentioning
confidence: 63%
“…Activation of WNT signaling in osteoclasts, osteoblasts, and cancer cells resulted in their conversion to tumor-suppressive cells with secretomes enriched with Hsp90ab1, enolase 1 (Eno1), moesin (MSN), and ubiquitin C (Ubc), which acted as atypical tumorsuppressors [204][205][206]. Osteoclast secretome-derived Hsp90ab1 and Eno1 inhibited tumor progression by suppressing TGF-ß signaling and interacting with CD44, facilitating tumor cell killing by natural killer (NK) cells [204,207]. They also exhibited bone-protective roles as osteoclast secretome inhibited RANKL-stimulated osteoclast differentiation and stimulated osteoblast differentiation.…”
Section: Novel Approaches To Treat Bone Metastasesmentioning
confidence: 99%